Does Mindfulness Training Have an Effect on Brain Tumor Patients? A Literature Review - Pujowati, Pujowati; Sarjono, Kalih; Syamsiah, Nita; Juniarni, Lia (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: The purpose of this research was to examine into the recent spike in curiosity regarding mindfulness-based therapy and their benefits on patients with brain tumors. Methods: The approach to searching was implemented by using certain keywords in an online database. This review's inclusion criteria were: (1) study of experimental design, (2) only brain tumor patients, and (3) Mindfulness-based therapy. The search was limited to English and Indonesian literature published between 2017 and 2023. To assess the quality of the included studies, the Critical Appraisal Skills Program (CASP) tool, which is available for intervention research, was employed. Results:  For this investigation, the original search method returned 581 documents. After a comprehensive study of these papers and application of the inclusion and exclusion criteria, four papers met the inclusion criteria. The programs lasted between 8 and 12 weeks. While mindfulness-based therapies revealed a good benefit for brain tumor patients, one study found a negative effect on family well-being. Conclusions: According to the journals reviewed, this study intends to evaluate the benefits of mindfulness training for improving the condition of brain tumor patients. The biological factors of the tumor or the participant's cognitive profile may influence improvement.